Microfinance services and membership of farmer-based organization as drivers of household food security among rice farmers in Niger and Nasarawa States, Nigeria - Otitoju, Moradeyo Adebanjo; Olaiya, Anuolu Queensly (Indonesian Journal of Agricultural Research, 2025)
Food security in Nigeria is a critical issue, with millions of farming households struggling daily. One potential solution is the provision of microfinance services and the promotion of membership in farmer-based organizations. This study examines the effect of these factors on the food security of 300 rice-farming households in Niger and Nasarawa States. Using descriptive and inferential statistics, ordered probit regression, and the household food insecurity access scale, the study reveals key findings: larger household sizes, older household heads, higher education levels, and larger farm sizes negatively affect food security. Conversely, membership of farmer-based organizations, access to microcredit and microsavings, extension services, farm income, and farming experience positively influence food security. The household food insecurity access scale (HFIAS) analysis shows that only 49% of rice-farming households in the study area are food secure. The study recommends expanding microfinance services, especially microcredit and microsavings, to improve food security among rice-farming households. Additionally, farmers should be encouraged to join farmer-based organizations to enhance their food security.